Technical efficiency of Southern African Customs Union ports: a data envelopment analysis approach - Weliswa Matekenya; Bekebu Siyanda (Journal of Shipping and Trade)
Abstract The growing demand for international trade and increasing port congestion have increased the need to improve technical efficiency in ports. While ocean ports are essential for facilitating global commerce, comprehensive analyses of the technical efficiency of African ports remain limited. This study assesses the technical efficiency of Southern African Customs Union (SACU) ports between 2014 and 2023 using Data Envelopment Analysis (DEA) and Tobit regression models to identify critical determinants of efficiency and inefficiency. The study is among the first to conduct a longitudinal, port-level efficiency analysis specifically focused on SACU countries, addressing a notable gap in empirical maritime research. The findings show significant disparities among SACU ports. Durban and Lüderitz demonstrate high efficiency due to their location, strategic investments, and advanced infrastructure, while ports like East London, Port Elizabeth, and Walvis Bay experience inefficiencies resulting from underutilised resources and inadequate infrastructure. The findings highlight strong correlations between port infrastructure, such as quay cranes, berths, and tugboats, as well as key performance indicators, such as container throughput and ship traffic. Inefficiencies are linked to poor management, misaligned port capacity, and scale issues. This study contributes to the literature on port efficiency by integrating DEA with Tobit regressions, a methodological combination that enhances diagnostic accuracy and enables a clearer understanding of the external factors influencing performance. Key outcomes include identification of performance benchmarks, infrastructure gaps, and actionable strategies that can guide targeted reforms in port operations. The results have practical implications for policymakers and port authorities, particularly in formulating strategies to optimise resources, improve infrastructure and enhance regional trade facilitation. The study emphasises the need for targeted infrastructure investments, operational improvements, and regulatory reforms to enhance port efficiency and regional trade competitiveness within the SACU region.